Topology Optimization of a PM Synchronous Machine Based on Novel Metaheuristic Algorithm for Lower Cogging Torque and Magnet Volume - Ruzbehi, Shabnam; Hahn, Ingo (Proceedings of the IEEE International Conference on Industrial Technology, 2022)
This paper proposes the Topology Optimization procedure of a three-phase permanent magnet synchronous motor (PMSM) to minimize weight, torque ripple and cogging torque, while preserving the average torque using a Binary Evolutionary Algorithm. To show the validity of the proposed topology optimization method, the design of the electrical machine's permanent magnet part is performed to enhance the merits of PMSM, with reduced production costs, lower permanent magnet consumption and improved motor performance. The magnetic field is calculated using the 2D finite element software FEMM in a discretized design area. The optimization process is done via MATLAB. The results show an improvement in the flux linkage and back-EMF waveform. Also, torque ripple and cogging torque reduction lead to less vibration and acoustic noise. The proposed topology optimization method can be extended to other active parts of the machine with different objective functions.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Back-EMF; Cogging torque; Genetic algorithms; PMSM; Topology optimization; Torque